2011
DOI: 10.1007/s00784-010-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

The German version of the Child Perceptions Questionnaire (CPQ-G11-14): translation process, reliability, and validity in the general population

Abstract: The aims of this study were to develop a German version of the Child Perceptions Questionnaire (CPQ11-14, a measure of oral health-related quality of life in 11-14-year-old children) and to assess the instrument's reliability and validity in German children ages 11-14. The English original version of the CPQ11-14 questionnaire was translated into German (CPQ-G11-14) by a forward-backward translation method. Reliability was investigated in 1,061 subjects aged 11-14 years from a regional sample (Wernigerode, Sax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
51
5
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 22 publications
10
51
5
4
Order By: Relevance
“…These results (ρ = 0.37 and 0.40 respectively) were similar to other studies (ρ = 0.38 and 0.39) (14) and (ρ = 0.35 and 0.32 respectively) (13). However, the validity scores were lower compared with studies evaluating oral health QoL in adults.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These results (ρ = 0.37 and 0.40 respectively) were similar to other studies (ρ = 0.38 and 0.39) (14) and (ρ = 0.35 and 0.32 respectively) (13). However, the validity scores were lower compared with studies evaluating oral health QoL in adults.…”
Section: Discussionsupporting
confidence: 88%
“…However, the Cronbach alpha coefficient in the current study (0.82) was high, as a reliability score greater than 0.5 is considered acceptable (20). This was similar to other studies (13,21), in which Cronbach alpha ranged between 0.81 and 0.91. This indicated that the short version of the Arabic questionnaire demonstrated good reliability scores for the total and subscale scores.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…For children aged 11 to 14 years, the Child Perceptions Questionnaire (CPQ11- 14) is one of the most sophisticated and most widely used instruments [2]. It has been cross-culturally adapted and administered in studies performed in different countries [3].…”
Section: Introductionmentioning
confidence: 99%